Sensory and chemical modifications of wine brandy aged with chestnut and oak wood - Caldeira, Ilda (2009)
This work evaluated the sensorial and chemical modifications in brandy aged in presence of two types of wood fragments in comparison with a brandy aged in wooden barrels.